Efektivitas Pemanfaatan Media Canva Untuk Meningkatkan Keterampilan Menulis Teks Deskripsi Siswa Kelas V SD Negeri 1 Kunden Karanganom Klaten - Retno Wulandari; Dwi Bambang Putut Setiyadi; Esti Ismawati; Hersulastuti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
ABSTRACTThe research question of this study is: How effective is the use of Canva media on the descriptive text writing skills of fifth-grade students at SD Negeri 1 Kunden Karanganom Klaten in the 2025/2026 Academic Year? This study aims to examine the effectiveness of Canva media in improving Indonesian descriptive text writing skills among fifth-grade students at SD Negeri 1 Kunden Karanganom Klaten. This study employed a quantitative approach using a quasi-experimental research design. The experimental method was used to determine the effect of a specific treatment under controlled conditions by comparing an experimental group and a control group. The experimental class was taught using Canva media, while the control class received instruction through conventional learning methods. This design enabled the researcher to identify causal relationships between the use of Canva media and students’ writing skills. The results of data analysis and hypothesis testing indicate that learning utilizing Canva media significantly affects students’ learning outcomes. Students in the experimental class achieved higher writing scores than those in the control class. The improvement in Indonesian writing skills showed that the experimental class reached a moderate category, while the control class remained in a low category. Statistical analysis revealed a calculated t-value of 4.21 with 28 degrees of freedom, which exceeded the t-table value of 1.70 at a 5% significance level. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (H1) was accepted. It can be concluded that the use of Canva media is effective in improving descriptive text writing skills of fifth-grade students at SD Negeri 1 Kunden Karanganom Klaten.Keywords: Effectiveness, Writing Skills, Canva MediaABSTRAKRumusan permasalahan dalam penelitian ini adalah bagaimana efektivitas pemanfaatan media Canva terhadap keterampilan menulis teks deskripsi pada siswa kelas V SD Negeri 1 Kunden Karanganom Klaten Tahun Pelajaran 2025/2026. Penelitian ini bertujuan untuk menguji efektivitas pemanfaatan media Canva dalam meningkatkan keterampilan menulis teks deskripsi Bahasa Indonesia pada siswa kelas V SD Negeri 1 Kunden Karanganom Klaten. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi eksperimen. Metode eksperimen diterapkan untuk mengetahui pengaruh suatu perlakuan terhadap variabel lain dalam kondisi yang terkendali dengan melibatkan dua kelompok, yaitu kelompok eksperimen dan kelompok kontrol. Kelompok eksperimen diberikan pembelajaran dengan memanfaatkan media Canva, sedangkan kelompok kontrol menggunakan metode pembelajaran konvensional. Hasil analisis data dan pengujian hipotesis menunjukkan bahwa pembelajaran dengan memanfaatkan media Canva berpengaruh terhadap keterampilan menulis siswa. Hasil belajar siswa pada kelas eksperimen lebih tinggi dibandingkan dengan kelas kontrol. Peningkatan keterampilan menulis Bahasa Indonesia pada kelas eksperimen berada pada kategori sedang, sedangkan pada kelas kontrol berada pada kategori rendah. Berdasarkan hasil uji t pada nilai post-test, diperoleh nilai t-hitung sebesar 4,21 dengan derajat kebebasan (df) 28, yang lebih besar daripada nilai t-tabel sebesar 1,70 pada taraf signifikansi 5%. Dengan demikian, Ho ditolak dan H1 diterima. Oleh karena itu, dapat disimpulkan bahwa pemanfaatan media Canva efektif dalam meningkatkan keterampilan menulis teks deskripsi Bahasa Indonesia siswa kelas V SD Negeri 1 Kunden Karanganom Klaten. Kata Kunci: Efektivitas, Keterampilan Menulis, Media Canva